Refill Water Management System Using an IoT-Based Water Flow Sensor - Sourideth, Phetsamone; Phonepaseuth, Phosy; Panthongsy, Khamphanh; Marie-Cécile, Péra (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
The primary and crucial use of water is as a drink. It is crucial for meeting the fluid needs of the human body. Dying from dehydration can occur when 15% of body weight is lost from not having enough water. Currently, numerous water refill points are accessible, sourced from both boreholes and mountain springs. Water is traditionally measured in transportation cars by filling the container without tracking the water input and output. This study aims to create a reusable water-filling control device that will track the inflow and outflow of water in the storage tank with the help of a Water Flow Sensor. The data obtained is based on analysis using the Arduino Uno in determine the volume of water, which is sent to the web server via the ESP8266 Wifi Module, providing the water volume information is shown directly on the management system app. Real-time viewing of the water volume data from the water flow sensor is possible in the refill water management app. After carrying out experiments; the 1,500 ml experiment showed the highest accuracy at 99.47%. The deviation of the 1,500 ml experiment is only 0.53%, showcasing the potential benefits of an automated water management system.